Changes in educational leadership: case study of a Hong Kong education centre. Issue 1 (2018) - Lau, Yui-yip
Educational leadership has paid significant attention to educational research over the past two decades. In Hong Kong, education centres are encountering both opportunities and challenges due to the globalisation, knowledge economy, demographic changes, international higher education development, local educational reform and global culture diversity characterising the new millennium. An appropriate leadership style ensures that Hong Kong education centres achieve quality, accountability and market competitiveness. Based on Fullan's (1999) work, in this study, we present a real-world case study of the changes sustained by a Hong Kong education centre. In particular, we focus on the ongoing changes (i.e., initiation, implementation and institutionalisation) in this centre under transformational leadership over a period of about five years to observe and examine the effectiveness and suitability of the leadership model. This study is designed to analyse the centre's management and changes under transformational leadership. The centre achieves sustainable competitive advantages in the new century.